A Streamlined Study on Chitosan-Zinc Oxide Nanomicelle Properties to Mitigate a Drug-Resistant Biofilm Protection Mechanism - Limayem, Alya; Patil, Shrushti B.; Mehta, Mausam; Cheng, Feng; Nguyen, Minh (Frontiers in Nanotechnology, 2020)
The nosocomial multidrug resistant bacteria (MDR), are rapidly circulating from water surfaces to humans away from the clinical setting, forming a cyclical breeding ground of resistance, causing worldwide infections, and thus requiring urgent responses. The combination of chitosan and zinc oxide (CZNPs), with proven bactericidal effects on some MDRs, was further studied to set the stage for a broad-spectrum in vivo utilization of CZNPs. Towards ensuring CZNPs’ uniformity and potency, when it faces not only biofilms but also their extracellular polymeric substances (EPS) defense mechanism, the size, zeta potential, and polydispersity index (PDI) were determined through dynamic light scattering (DLS). Furthermore, the efficacy of CZNPs was tested on the inhibition of MDR Gram-negative Escherichia coli BAA-2471 and Gram-positive Enterococcus faecium 1449 models, co-cultured in an Alvatex 3D fiber platform as a biofilm-like structure. The Biotek Synergy Neo2 fluorescent microplate reader was used to detect biofilm shrinkage. The biofilm protection mechanism was elucidated through detection of EPS using 3D confocal and transmission electronic microscopy. Results indicated that 200 µl/mL of CZNPs, made with 50 nm ZnO and 10,000 Da chitosan (N=369.1 nm; PDI = 0.371; zeta potential = 22.8 mV), was the most promising nanocomposite for MDR biofilm reduction, when compared to CZNPs enclosing ZnO, 18nm or 100 nm. This study depicts that CZNPs possess enough potency and versatility to face biofilms’ defense mechanism in vivo.